She Fought Against Coal: Women and Children of Coal-Free Bataan Movement - Almira, Kathryn Narciso (Indonesian Journal of Law and Society, 2024)
The latest World Risk Index ranked the Philippines as the most disaster-prone country in the world. Each year, around 20 typhoons on average batter the Philippine archipelago, which straddles the typhoon belt and the Ring of Fire in the Pacific. Despite the looming threats of disasters, the country’s continued reliance on coal to meet its power needs exacerbates the existing impacts of climate change. For the poorest and most vulnerable children and families who have the least ability to cope, the devastating consequences may hit the hardest and the longest. Framing the climate crisis through a human rights lens, this engaged research draws upon ethnographic and archival research to explore the gradual injuries of living along the fenceline of a coal-fired power plant and situate the findings within the framework of environmental justice in light of the “sana-dapat” (human rights) of women and children in the coal-affected community of Lamao in Limay, Bataan. This paper expands the analysis of the findings through Nixon’s notion of slow violence (2011), which is “a violence of delayed destruction that is dispersed across time and space,” highlighting the intergenerational persistence of toxins that may result in flow-on effects even in land, water, and human bodies, including unborn babies. Elaborating the temporal and spatial complexity of the cumulative harms of toxic pollution to human and environmental health, the study further examines how the everyday burdens of coal produce the conditions for grassroots action among women and children, and contribute to the growing climate justice movement in the country. Keywords: environmental justice, slow violence, human rights, coal pollution, climate change